A new weevil (Coleoptera; Nemonychidae; Oropsini trib. nov.) from Lower Cretaceous Lebanese amber. (February 2017) - Legalov, Andrei A.; Azar, Dany; Kirejtshuk, Alexander G.
Abstract: A new weevil, Oropsis marinae gen. et sp. nov., Oropsini trib. nov., is described from Lower Cretaceous Lebanese amber. The new genus is similar to the genera Libanorhinus Kuschel et Poinar, 1993 and Arra Peris, Davis et Delclòs, 2014. It differs from Libanorhinus in the long abdominal ventrite 1, prosternal process distinctly extends beyond procoxal cavities and tarsomere 3 weakly bilobed, and from Arra in the arcuate pronotal sides, antennal club with fused articles, long abdominal ventrite 1, procoxal cavities probably open posteriorly, and tarsal claws without teeth. Oropsini trib. nov. differs from the tribes Paleocartini, Selengarhynchini and Metrioxenoidini in the transversely oval and separated procoxal cavities, weakly convex and oval eyes, and the trochanters completely separating femora and coxae.